Embrapa e a pesquisa técnico-científica no perímetro irrigado Jaguaribe-Apodi/CE - Oliveira, Maria Rosana da Costa (2012)
This paper discusses the performance of decentralized units of the Brazilian Agricultural Research Corporation (EMBRAPA) - Tropical Agribusiness - within the Irrigation Jaguaribe-Apodi, in the county of Limoeiro do Norte. Located in Fortaleza, the performance of this unit is established primarily agricultural areas along the dynamic state of Ceará. Among the areas of activity, in the present study highlight the Irrigated Perimetro Irrigado Jaguaribe-Apodi. Considered one of the public projects of irrigated agriculture in the most advanced stage in the northeast and production technology level, set up to Embrapa as a true "laboratory" to open the development and application of technologies developed by it. Besides the large and medium enterprises, small farmers find the perimeter which contradicts the lack of state incentives continue to produce rainfed crops (beans and corn ). The research discusses therefore the discontinuities techniques in this space, resulting from the work developed by Embrapa and the educational centers, which directs its research and services predominantly to large companies producing fruit. Throughout the dissertation, we question the role of the state as Embrapa, since its primary mission would be "feasible solutions research, development and innovation for sustainable agriculture for the benefit of Brazilian society."